Hemoglobin A1c values are affected by hemoglobin level and gender in non‐anemic Koreans. Issue 1 (5th August 2013) - Bae, Ji Cheol; Suh, Sunghwan; Jin, Sang‐Man; Kim, Se Won; Hur, Kyu Yeon; Kim, Jae Hyeon; Min, Yong‐Ki; Lee, Myung‐Shik; Lee, Moon Kyu; Jeon, Won Seon; Lee, Won Young; Kim, Kwang‐Won
Abstract Aims/Introduction To evaluate whether hemoglobin A1c (HbA1c) levels are affected by hemoglobin level and gender. Materials and Methods A cross‐sectional analysis was carried out in a sample of 87, 284 non‐diabetic Koreans without anemia who participated in comprehensive health check‐ups between January and December 2009 at the Kangbuk Samsung Hospital Total Healthcare Center in Seoul, Korea. We categorized men and women separately according to fasting plasma glucose and hemoglobin level to carry out the analysis. Results HbA1c increased steadily with increasing fasting plasma glucose level. Both men and women with lower hemoglobin had significantly higher HbA1c at a given fasting glucose level, and this result was consistent across the fasting glucose quintiles within the non‐diabetic range. Women had a lower mean hemoglobin value compared with men, and women had higher HbA1c levels at a given fasting glucose level consistently across the fasting glucose deciles. There was also a gender‐specific association between age and HbA1c (P < 0.001 for interaction). Conclusions HbA1c values were affected by hemoglobin level and gender in non‐anemic Koreans. Thus, hemoglobin level and gender should be considered in the diagnosis of diabetes using HbA1c.